2012
DOI: 10.1590/s0100-39842012000500015
|View full text |Cite
|
Sign up to set email alerts
|

Rânula congênita: diagnóstico ultrassonográfico antenatal

Abstract: A congenital ranula is a rare cystic malformation seen in the oral cavity. This pseudocyst is normally located in the sublingual space between the mylohyoid muscle and the lingual mucosa. A 24-year-old woman, gravida 3, para 2, at 29 weeks' gestation was referred to our institution because of polihydramnios and large oral mass. Keywords: Prenatal diagnosis; Ultrasound; Oral tumor; Ranula.Rânula congênita uma rara malformação cística visualizada na cavidade oral. É um pseudocisto habitualmente localizado no esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the present case, the authors have also observed placentomegaly, but without cystic areas. Prenatal and neonatal ultrasonography has been utilized for many years in the assessment of fetal malformations (7)(8)(9) . 3DUS in rendering mode has clearly demonstrated the remarkable fetal abdominal distension and macroglossia.…”
Section: Bws Was First Described By Beckwith In 1963 and Bymentioning
confidence: 99%
“…In the present case, the authors have also observed placentomegaly, but without cystic areas. Prenatal and neonatal ultrasonography has been utilized for many years in the assessment of fetal malformations (7)(8)(9) . 3DUS in rendering mode has clearly demonstrated the remarkable fetal abdominal distension and macroglossia.…”
Section: Bws Was First Described By Beckwith In 1963 and Bymentioning
confidence: 99%